Global Approaches to Early Learning Research and Practice: Integrative Commentary. Issue 158 (15th December 2017) - Landi, Nicole; Cutting, Laurie E.
Abstract: This commentary presents highlights from the seven articles in this volume, along with a synthesis of take‐home points that can be used to inform policy and practice. Across each article there is a story of both successes and the challenges of ongoing work that seeks to enhance children's development in diverse and challenging environments across the globe. Although the topics covered in this volume range from development of early self‐regulation and executive function to the use of technology to aid literacy acquisition in remote areas, each points to the need for systems‐level coordination and sustained commitment to reach children at risk.